2020
DOI: 10.1097/mcg.0000000000001317
|View full text |Cite
|
Sign up to set email alerts
|

Deprescribing Proton Pump Inhibitors in an Academic, Primary Care Clinic

Abstract: Goals:To reduce the percentage of inappropriately prescribed proton pump inhibitors (PPIs) in patients aged 50 and older from 80% (baseline) to 60% within 12 months in an academic, internal medicine clinic. Background:The use of PPIs has increased drastically worldwide. Internal medicine clinic patients had inappropriate use of PPIs for an average of 4-5 years. Study:A multidisciplinary quality improvement team used the Plan-Do-Study-Act Model of health care improvement and performed a root cause analysis to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Nallapeta et al (Nallapeta, Reynolds and Bakhai, 2020) used the American Gastroenterological Association (AGA) guidelines to identify those patients who were taking PPIs inappropriately. The registry used in this study was the electronic medical record.…”
Section: Resultsmentioning
confidence: 99%
“…Nallapeta et al (Nallapeta, Reynolds and Bakhai, 2020) used the American Gastroenterological Association (AGA) guidelines to identify those patients who were taking PPIs inappropriately. The registry used in this study was the electronic medical record.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, the multi-faceted Australian national quality improvement programs that also included patient education material contributed to reducing PPI use in older adults by 21% [ 19 ]. In 2020, several interventional cycles in the United-States included patient education pamphlets and discontinued inappropriate chronic PPI use by 30% within 12 months [ 20 ]. Based on these previous studies in Australia, Ireland and United-States, we anticipate that involving patients in the deprescribing process using an education brochure should improve the PPI deprescribing rate.…”
Section: Discussionmentioning
confidence: 99%
“…Using an intraclass correlation coefficient (ICC) of 0.05 thus lead to an inflation factor of 3.365. Literature data suggested a “natural” PPI deprescribing rate between 2 and 7% in the control arm [ 17 , 20 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of inappropriate PPI prescription range from 27 to 81% in hospitalized patients and 36 to 63% in patients in primary care settings [ 14 ]. Multiple strategies have been described to identify PPI overuse and reduce rates of inappropriate prescription, including provider education initiatives and guideline-driven medication review by independent pharmacists and gastroenterologists [ 33 , 34 , 35 ]. While some studies have reported success with such strategies, the role of patient education in reducing inappropriate PPI use has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%